What hinders and helps academics to conduct Dissemination and Implementation (D&I) research in the field of nutrition and physical activity? An international perspective - Harriet Koorts; Patti-Jean Naylor; Rachel Laws; Penelope Love; Jaimie-Lee Maple; Femke van Nassau (BMC, 2020)
Abstract Background Ineffective research-practice translation is a major challenge to population health improvement. This paper presents an international perspective on the barriers and facilitators associated with the uptake of and engagement in Dissemination and Implementation (D&I) research in the fields of physical activity and nutrition. Methods A mixed methods study involving participants from the International Society for Behavioral Nutrition and Physical Activity (ISBNPA) network. Participants completed an online survey (May-July 2018) and/or participated in a focus group during the annual ISBNPA conference (June 2018). Descriptive statistics were generated for quantitative online and pre-focus group survey data. Fisher's exact tests investigated associations of (i) length of time in academia, (ii) career stage and (iii) country of work, and agreement with 'perceptions of D&I'. Qualitative data were analysed thematically. Results In total, 141 participants responded to the survey (76% female, 21% aged 35-39 years, 14 countries represented) and 25 participated in focus groups (n = 3). Participants self-identified as having knowledge (48%), skills (53%) and experience supporting others (40%) to conduct D&I research. The majority (96%) perceived D&I was important, with 66% having organizational support for D&I, yet only 52% reported prioritizing D&I research. Perceptions of D&I differed by length of time in academia, career stage and country of work. Barriers included: (i) lack of D&I expertise; (ii) lack of organisational support/value for D&I; (iii) embedded scientific beliefs/culture; (iv) methodological challenges with D&I research; (v) funding/publishing priorities and; (vi) academic performance structures. Facilitators included: (i) increased presence/value of D&I; (ii) collective advocacy; (iii) organisational support for D&I; (iv) recruitment of D&I scientists and; (v) restructure of academic performance models, funding/publishing criteria. Conclusions Individual, organisational and system-wide factors hindered academics' engagement with and support for D&I research, which was perceived to reduce opportunities for research-practice translation. Factors were mostly consistent across countries and individual career stages/time spent in academia. Embedding D&I early within academic training, and system-wide reorientation of academic performance and funding structures to promote and facilitate D&I research, are some of the necessary actions to reduce the research-practice gap. Consistent with public health more broadly, these changes are long overdue in the fields of physical activity and nutrition.